Positive electrode active material for lithium secondary battery and lithium secondary battery using same

By preparing the lithium composite phosphorus oxide positive electrode active material with bimodal particle size distribution, the problems of increased capacity and poor energy density of positive electrode active material in lithium secondary batteries are solved, and the effect of high energy density and uniform carbon-based coating is achieved.

CN119905542APending Publication Date: 2025-04-29ECOPRO BM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411341047.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-26
Filing Date
2024-09-25
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The demand for increasing the capacity of positive electrode active substances in lithium secondary batteries is difficult to meet, and the existing nano-nanized lithium iron phosphate is prone to aggregation due to the mutual attraction between particles, resulting in poor energy density, carbon coating reduces fluidity and reduces density.

Method used

The slurry is prepared by mixing lithium-containing raw materials, iron-containing precursors, dopant-containing raw materials, sodium-containing raw materials and carbon-based compounds, crushing and heat treatment to prepare lithium composite phosphorus oxides and positive electrode active substances with bimodal particle size distribution.

Benefits of technology

High particle density, excellent energy density, and large particles are formed at low calcining temperatures, using a minimum amount of carbon-based compounds to form a uniform carbon-based coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905542A_ABST
    Figure CN119905542A_ABST
Patent Text Reader

Abstract

The present specification relates to a method for preparing a positive electrode active material for a lithium secondary battery, and more particularly, to a method for preparing a positive electrode active material for a lithium secondary battery having excellent conductivity and energy density, a positive electrode including the same, and a secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present specification relates to a method for preparing a positive electrode active material for a lithium secondary battery, and more specifically, to a method for preparing a positive electrode active material for a lithium secondary battery having excellent electrical conductivity and energy density. Background Art

[0002] Batteries store electrical energy using materials capable of electrochemical reactions at the positive and negative electrodes. A typical example of such batteries is a lithium secondary battery that stores electrical energy by using the chemical potential difference when lithium ions are inserted / released between the positive and negative electrodes.

[0003] The lithium secondary battery is prepared by using a substance capable of reversibly inserting and extracting lithium ions as a positive electrode active material and a negative electrode active material, and filling an organic electrolyte or a polymer electrolyte between the positive electrode and the negative electrode.

[0004] A variety of materials are used as positive electrode active materials for lithium secondary batteries, among which lithium metal phosphates, such as lithium iron phosphate (LiFePO4), are widely used in the manufacture of lithium secondary batteries due to their excellent stability and ability to withstand multiple charge / discharge cycles and relatively low manufacturing cost.

[0005] However, due to the properties of lithium iron phosphate's olivine crystal structure, lithium ions can only diffuse in one dimension, resulting in low ionic conductivity and electrical conductivity. Therefore, there are technologies that attempt to nanosize lithium iron phosphate particles and perform carbon coating to improve these shortcomings.

[0006] However, nanosized lithium iron phosphate tends to aggregate due to the mutual attraction between particles and tends to grow into a shape that is not conducive to energy density.

[0007] Furthermore, carbon coating reduces the fluidity of lithium iron phosphate particles, which results in a decrease in the density of the positive electrode active material.

[0008] As technology develops, the demand for lithium secondary batteries, including electric vehicles, is increasing dramatically, and the demand for increased capacity of lithium secondary batteries, which is directly related to the usage time of products, is also growing in related industries. Summary of the invention

[0009] Technical issues

[0010] In the lithium secondary battery market, the growth of lithium secondary batteries for electric vehicles plays a leading role in the market, and the demand for positive electrode active materials used in lithium secondary batteries is also changing. In particular, the demand for increased capacity of positive electrode active materials is gradually increasing.

[0011] In order to meet these market demands, an object of the present specification is to provide a method for preparing a positive electrode active material which is advantageous in terms of energy density due to having a bimodal particle size distribution including small particles and large particles.

[0012] In addition, the present specification aims to provide a positive electrode comprising a positive electrode active material prepared according to the preparation method defined herein.

[0013] Furthermore, the present specification aims to provide a lithium secondary battery using the positive electrode defined herein.

[0014] Solutions to the problem

[0015] According to one aspect of the present specification, a method for preparing a positive electrode active material for a lithium secondary battery is provided, comprising: step (a), preparing a slurry by mixing a lithium-containing raw material, an iron-containing precursor, a dopant-containing raw material, a sodium-containing raw material and a carbon-based compound; step (b), crushing particles in the above slurry; and step (c), heat-treating the crushed particles to obtain a lithium composite phosphorus oxide; the above dopant is at least one selected from the group consisting of Ag, Al, As, Au, Ba, Be, Bi, Ca, Cd, Ce, Co, Cr, Cu, Ga, Hf, In, K, La, Mg, Mo, Nb, Nd, Ni, Os, Pd, Pr, Pt, Rh, Ru, Si, Sm, Sn, Sr, Ta, Ti, V, W, Y, Zn and Zr.

[0016] In one embodiment, in the slurry in the step (a), the ratio (Li / Metal) of the number of lithium atoms (Li) to the total number of metal atoms (Metal) other than lithium may be 0.95 to 1.05.

[0017] In addition, in the slurry in the step (a), the ratio (Fe / Metal) of the number of atoms of iron (Fe) to the total number of atoms of metal elements other than lithium (Metal) may be 0.96 to 0.98.

[0018] Wherein, in the slurry in the step (a), the ratio (D / Metal) of the number of atoms of the dopant (D) to the total number of atoms of the metal elements (Metal) other than lithium may be 0.02 to 0.03.

[0019] On the other hand, in the slurry in the step (a), the ratio (Na / Metal) of the number of atoms of sodium (Na) to the total number of atoms of metal elements other than lithium (Metal) may be 0 to 0.01.

[0020] Furthermore, in the step (a), at least one of the dopant-containing raw material and the sodium-containing raw material may be at least one selected from the group consisting of sulfates, carbonates, nitrates, acetates, chlorides, hydroxides and oxides.

[0021] In addition, in the slurry in the step (a), a ratio (C / Metal) of the number of carbon atoms (C) to the total number of metal atoms (Metal) other than lithium may be 0.25 to 1.5.

[0022] In another embodiment, the particles crushed in the step (c) may be obtained by spray drying the slurry obtained in the step (b).

[0023] Furthermore, the heat treatment in the above step (c) may be performed at a maximum temperature of 600° C. to 900° C. for 5 hours to 15 hours in an inert atmosphere.

[0024] According to another aspect of the present specification, there is provided a positive electrode active material for a lithium secondary battery, which is a positive electrode active material including a lithium composite phosphorus oxide capable of lithium insertion / deinsertion, wherein the lithium composite phosphorus oxide includes secondary particles formed by agglomeration of a plurality of primary particles, the primary particles having a bimodal form including a first lithium composite phosphorus oxide as small particles and a second lithium composite phosphorus oxide as large particles, at least one of the first lithium composite phosphorus oxide and the second lithium composite phosphorus oxide including iron, a dopant and a sodium element, the dopant being at least one selected from the group consisting of Ag, Al, As, Au, Ba, Be, Bi, Ca, Cd, Ce, Co, Cr, Cu, Ga, Hf, In, K, La, Mg, Mo, Nb, Nd, Ni, Os, Pd, Pr, Pt, Rh, Ru, Si, Sm, Sn, Sr, Ta, Ti, V, W, Y, Zn and Zr, and an amorphous carbon coating having a thickness of 1 nm to 500 nm is formed on the surface of at least a portion of the primary particles.

[0025] In addition, the content of the second lithium composite phosphorus oxide in the positive electrode active material may be 10 wt % to 20 wt %.

[0026] On the other hand, the lithium composite phosphorus oxide can be represented by the following Chemical Formula 2.

[0027] [Chemical formula 2]

[0028] Li p Fe (1-y-z) M y Na z PO4

[0029] In the above formula, M is at least one selected from the group consisting of Ag, Al, As, Au, Ba, Be, Bi, Ca, Cd, Ce, Co, Cr, Cu, Ga, Hf, In, K, La, Mg, Mo, Nb, Nd, Ni, Os, Pd, Pr, Pt, Rh, Ru, Si, Sm, Sn, Sr, Ta, Ti, V, W, Y, Zn and Zr, 0.95≤p≤1.05, 0.02≤y≤0.03, 0≤z≤0.01.

[0030] According to another aspect, a positive electrode including the positive electrode active material is provided.

[0031] According to still another aspect, a lithium secondary battery using the positive electrode is provided.

[0032] Effects of the Invention

[0033] According to the present specification, when preparing a lithium composite phosphorus oxide by calcining a raw material, by including a specific doping element, a bimodal positive electrode active material containing both small particles and large particles can be prepared in one synthesis process.

[0034] In addition, when the above-mentioned positive electrode active material is prepared, large particles can be formed even at a low calcination temperature, and thus a uniform carbon-based coating layer can be formed with a minimum amount of the carbon-based compound.

[0035] Therefore, the positive electrode active material has a high particle density and can have an excellent energy density.

[0036] In addition to the above-described effects, specific effects of the present specification will be described while explaining specific details of the present specification. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The secondary particle size distribution of the positive electrode active material prepared according to one embodiment of the present specification.

[0038] Figure 2 1 is the primary particle size distribution of the positive electrode active material prepared according to one embodiment of the present specification. DETAILED DESCRIPTION

[0039] Specific terms are defined herein to facilitate understanding of this specification. Unless specifically defined herein, scientific terms and technical terms used herein should have the meanings commonly understood by those skilled in the art. In addition, it should be understood that as used herein, unless the context clearly indicates otherwise, the singular form is intended to include the plural form, and vice versa.

[0040] Hereinafter, a method for preparing a positive electrode active material for a lithium secondary battery according to the present specification, a positive electrode including the positive electrode active material prepared according to the preparation method, and a lithium secondary battery using the positive electrode will be described in more detail.

[0041] Method for preparing positive electrode active material for lithium secondary battery

[0042] According to one aspect, a method for preparing a positive electrode active material for a lithium secondary battery includes: step (a), preparing a slurry by mixing a lithium-containing raw material, an iron-containing precursor, a dopant-containing raw material, a sodium-containing raw material and a carbon-based compound; step (b), crushing particles in the above slurry; and step (c), heat-treating the crushed particles to obtain a lithium composite phosphorus oxide; the above dopant can be at least one selected from the group consisting of Ag, Al, As, Au, Ba, Be, Bi, Ca, Cd, Ce, Co, Cr, Cu, Ga, Hf, In, K, La, Mg, Mo, Nb, Nd, Ni, Os, Pd, Pr, Pt, Rh, Ru, Si, Sm, Sn, Sr, Ta, Ti, V, W, Y, Zn and Zr.

[0043] The above step (a) is a step of preparing an aqueous solution slurry by mixing a raw material for preparing a lithium composite phosphorus oxide with water.

[0044] The lithium-containing raw material used in the above step (a) is used to form a lithium complex phosphorus oxide used as a positive electrode active material, and lithium hydroxide, lithium carbonate, lithium nitrate, lithium phosphate, lithium fluoride or lithium acetate can be used.

[0045] At this time, mixing can be performed so that the ratio (Li / Metal) of the number of lithium atoms (Li) in the above-mentioned slurry of the above-mentioned lithium compound to the total number of metal atoms (Metal) other than lithium is in the range of 0.95 to 1.05, for example, it can be 0.95, 0.96, 0.97, 0.98, 0.99, 1.00, 1.01, 1.02, 1.03, 1.04, 1.05 or a range between any two of these values.

[0046] On the other hand, the iron-containing precursor is a precursor material of a lithium-phosphorus composite oxide containing an iron element, and can react with a lithium-containing raw material to form a lithium-phosphorus composite oxide.

[0047] In one example, in addition to iron, the iron-containing precursor may also contain at least one transition metal such as manganese, nickel, cobalt, vanadium, titanium, chromium, copper, zinc, etc. and at least one element such as phosphorus, oxygen, hydrogen, carbon, silicon, sulfur, nitrogen, boron, fluorine, chlorine, iodine, etc.

[0048] Optionally, the iron-containing precursor may be doped with a foreign element. Here, the foreign element may be at least one selected from the group consisting of Ag, Al, As, Au, B, Ba, Be, Bi, Ca, Cd, Ce, Co, Cr, Cu, F, Ga, Hf, I, In, K, La, Mg, Mo, N, Na, Nb, Nd, Ni, Os, Pd, Pr, Pt, Rh, Ru, Si, Sm, Sn, Sr, Ta, Ti, V, W, Y, Zn and Zr.

[0049] As an example, the iron-containing precursor may be an iron composite hydroxide or an iron composite oxide containing iron, or an iron composite phosphorus oxide containing iron and phosphorus.

[0050] The iron composite hydroxide precursor can be prepared by a synthesis reaction in an aqueous solution containing an iron raw material.

[0051] As an example of the above-mentioned synthesis reaction, the iron composite hydroxide precursor can be prepared by adding dropwise an alkaline aqueous solution while stirring an aqueous solution containing an iron raw material, a phosphorus raw material, and an oxidizing agent.

[0052] Here, the amount of the iron raw material, phosphorus raw material and oxidant added can be changed according to the composition of the desired positive electrode active material. For example, when preparing LiFePO4, the iron raw material, phosphorus raw material and oxidant can be added so that the difference in the amount of addition is less than 20% of each other on a molar basis, for example, 20%, 15%, 10% or a range between two of these values, but not limited thereto.

[0053] In another example, the molar ratios of the iron raw material, the phosphorus raw material and the oxidant may be 0.8-1.2:0.8-1.2:0.8-1.2, i.e., 0.8, 0.85, 0.9, 0.95, 1, 1.05, 1.1, 1.15, 1.2 or a molar ratio in a range between two of these values, but are not limited thereto.

[0054] Here, examples of the above-mentioned iron raw material include ferrous sulfate, ferrous oxalate, ferric citrate, ferric hydroxide, ferric phosphate, ferric chloride, ferric nitrate, ferric acetate and the like.

[0055] On the other hand, as the phosphorus raw material, phosphoric acid, iron phosphate, lithium dihydrogen phosphate, lithium phosphate, ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, phosphorus pentoxide, and the like can be used.

[0056] In addition, examples of the above-mentioned oxidizing agent include hydrogen peroxide, glycolic acid, citric acid, ammonium persulfate, sodium persulfate, potassium persulfate, potassium permanganate, ammonium persulfate, nitric acid, chloric acid, chromic acid, manganese dioxide, ferric chloride and the like.

[0057] As the alkaline aqueous solution, a sodium hydroxide aqueous solution, an ammonia aqueous solution, a potassium hydroxide aqueous solution, or the like can be used.

[0058] The above-mentioned alkaline aqueous solution is added to an aqueous solution in which an iron raw material, a phosphorus raw material and an oxidant are added to pure water (DIW), and the reaction is carried out at a temperature of 40°C to 80°C, for example, at 40°C, 42.5°C, 45°C, 47.5°C, 50°C, 52.5°C, 55°C, 57.5°C, 60°C, 62.5°C, 65°C, 67.5°C, 70°C, 72.5°C, 75°C, 77.5°C, 80°C or a temperature in a range between any two of these values, to prepare a hydroxide precursor.

[0059] The above reaction can be carried out under inert conditions, for example, in a reaction system substituted with at least one inert gas selected from the group consisting of N2, Ar, He, Rn, Ne and Xe, but is not limited thereto.

[0060] On the other hand, as necessary, a raw material containing a foreign element may be further added to dope the hydroxide precursor with the foreign element.

[0061] The iron composite oxide precursor can be prepared by heat-treating the above-mentioned iron composite hydroxide precursor.

[0062] Here, the iron composite oxide precursor may be heat-treated in a calcining furnace at 400° C. to 700° C., for example, 400° C., 425° C., 450° C., 475° C., 500° C., 525° C., 550° C., 575° C., 600° C., 625° C., 650° C., 675° C., 700° C., or the highest temperature within any two temperature ranges therebetween, for 3 hours to 10 hours, for example, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, 8 hours, 8.5 hours, 9 hours, 9.5 hours, 10 hours, or any two times within these time ranges, but is not limited thereto.

[0063] On the other hand, the heat treatment is performed at a temperature increase rate of 1°C to 5°C per minute, for example, at a temperature increase rate of 1°C, 1.5°C, 2°C, 2.5°C, 3°C, 3.5°C, 4°C, 4.5°C, 5°C or a range between any two of these values ​​per minute, so that the above maximum temperature can be reached. In addition, the heat-treated precursor can be obtained by furnace cooling.

[0064] Using the iron composite oxide precursor prepared in this manner, nano primary particles having an olivine crystal structure can be formed.

[0065] As a specific example, the above-mentioned iron composite oxide precursor is prepared by the following steps: step (i), preparing an iron composite hydroxide precursor by adding an alkaline aqueous solution to a reaction system containing an iron raw material, a phosphorus raw material and an oxidant; and step (ii), preparing an iron composite oxide precursor by heat treating the above-mentioned iron composite hydroxide precursor, but is not limited to this.

[0066] On the other hand, the slurry in the above step (a) may include a raw material containing a dopant, so that the lithium composite phosphorus-phosphorus oxide may be doped with a foreign element.

[0067] Here, in the slurry in the step (a), a ratio (Fe / Metal) of the number of atoms of iron (Fe) to the total number of atoms of metal elements (Metal) excluding lithium may be 0.96 to 0.98.

[0068] As olivine-based positive electrode materials, lithium iron phosphate-based compounds have PO4 3- The strong covalent bond of Li has a relatively low conductivity. In addition, it is known that due to its crystal structure, Li + Only one-dimensional diffusion is possible, so its ionic conductivity is low.

[0069] As a means to solve these shortcomings, it has been proposed to improve the Li + Diffusion of technology.

[0070] However, the above-mentioned technology reduces the density of the positive electrode active material, and as a result, the energy density of the final product may be reduced.

[0071] One way to increase the density of the positive electrode active material is to mix particles of different sizes.

[0072] For example, it is known that a positive electrode active material showing a bimodal particle distribution in which a particle size distribution diagram is mixed so as to have two peaks can have a high density.

[0073] Conventionally, in order to prepare such a positive electrode active material, two materials having different average particle sizes are mixed.

[0074] However, in the above method, since the lithium composite phosphorus oxide is synthesized at a high calcination temperature during the preparation of large particles, the carbon-based compound is lost during the calcination process, resulting in different properties of the carbon-based coating between large particles and small particles. In addition, in order to form the carbon-based coating, a larger amount of carbon-based compound is required.

[0075] On the other hand, in the above method according to one aspect of the present specification, the particle size of the primary particles of the synthesized lithium composite phosphorus oxide can be controlled by using a specific dopant or sodium that can function as a flux that affects particle growth.

[0076] Among them, the above-mentioned dopant can be at least one selected from the group consisting of Ag, Al, As, Au, Ba, Be, Bi, Ca, Cd, Ce, Co, Cr, Cu, Ga, Hf, In, K, La, Mg, Mo, Nb, Nd, Ni, Os, Pd, Pr, Pt, Rh, Ru, Si, Sm, Sn, Sr, Ta, Ti, V, W, Y, Zn and Zr.

[0077] The above-mentioned dopant can realize a bimodal form by growing specific particles of the above-mentioned lithium composite phosphorus oxide or inhibiting the growth without physical mixing.

[0078] In addition, the dopant may improve the stability or electrical conductivity of the lithium composite phosphorus oxide.

[0079] Wherein, in the slurry in the step (a), the ratio (D / Metal) of the number of atoms of the dopant (D) to the total number of atoms of the metal elements (Metal) other than lithium may be 0.02 to 0.03.

[0080] On the other hand, the slurry in the step (a) may contain a sodium-containing raw material to dope the lithium composite phosphorus oxide with sodium.

[0081] When the lithium composite phosphorus oxide is doped with sodium, large particles of 3 μm to 20 μm can be formed.

[0082] On the other hand, the sodium element can improve the lattice stability of the lithium composite phosphorus oxide.

[0083] Here, in the slurry in the step (a), a ratio (Na / Metal) of the number of atoms of sodium (Na) to the total number of atoms of metal elements other than lithium (Metal) may be 0 to 0.01.

[0084] In addition, in the step (a), at least one of the dopant-containing raw material and the sodium-containing raw material may contain hydrogen and oxygen.

[0085] That is, at least one of the above-mentioned dopant-containing raw material and the above-mentioned sodium-containing raw material can be composed of A(O a H b ) c (wherein A is an element having an oxidation number of +1 or +2).

[0086] On the other hand, in another example, the dopant-containing raw material and the sodium-containing raw material may be at least one selected from the group consisting of sulfates, carbonates, nitrates, acetates, chlorides, hydroxides, and oxides.

[0087] When a raw material containing a dopant or sodium is introduced into the slurry, the particle size of the lithium composite phosphorus oxide can be controlled.

[0088] As a method of improving the electrical conductivity of a lithium iron phosphate-based compound, a technique of forming a carbon coating on at least a portion of the surface has been proposed.

[0089] However, the coated carbon exists in an amorphous phase, thereby possibly reducing the density of the positive electrode active material.

[0090] When the thickness of the carbon coating layer is minimized while increasing its uniformity, a decrease in fluidity due to amorphous carbon can be minimized, and the conductivity of the positive active material can be improved.

[0091] The carbon-based compound contained in the slurry in the above step (a) may be used to form a carbon coating layer that improves the electrical conductivity of the positive electrode active material.

[0092] Examples of the above-mentioned carbon-based compounds include sucrose, glucose, polyvinyl alcohol (PVA), polyvinyl pyrrolidone (PVP), colloidal carbon, citric acid, tartaric acid, glycolic acid, polyacrylic acid, adipic acid, glycine, aminobenzoic acid, etc., but are not limited thereto.

[0093] As an example, the above-mentioned carbon-based compound can be added so that the ratio (C / Metal) of the number of carbon atoms (C) in the above-mentioned slurry to the total number of metal atoms (Metal) other than lithium is in the range of 0.25 to 1.5, for example, it can be 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.95, 1.00, 1.05, 1.10, 1.15, 1.20, 1.25, 1.30, 1.35, 1.40, 1.45, 1.50 or a range between any two of these values.

[0094] For example, the above-mentioned carbon-based compound can be added so that the content of the carbon coating in the final product is 1.0 wt% to 2.0 wt%, for example, 1.0 wt%, 1.05 wt%, 1.1 wt%, 1.15 wt%, 1.2 wt%, 1.25 wt%, 1.3 wt%, 1.35 wt%, 1.4 wt%, 1.45 wt%, 1.5 wt%, 1.55 wt%, 1.6 wt%, 1.65 wt%, 1.7 wt%, 1.75 wt%, 1.8 wt%, 1.85 wt%, 1.9 wt%, 1.95 wt%, 2.0 wt%, or a range between any two of these values, based on 100 wt% of the lithium composite phosphorus oxide.

[0095] If the content of the carbon-based compound in the slurry satisfies the above range, a thin carbon coating layer can be easily formed.

[0096] On the other hand, the above-mentioned carbon-based compound can be a compound having a C element ratio in the molecular structure of 30% to 60% by weight, for example, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60% by weight, or a range between any two of these values.

[0097] By using a carbon-based compound having a ratio of the C element satisfying the above range, a product having excellent yield and carbon coating uniformity can be prepared even if the same content of the compound is used.

[0098] In addition, since the above-mentioned preparation method uses a wet coating method to form the carbon coating layer, it is necessary to use a raw material having sufficient solubility in water.

[0099] Therefore, the solubility of the above-mentioned carbon-based compounds in water at 25°C can be 0 g / L to 3,000 g / L, for example, 3,000 g / L, 2,750 g / L, 2,500 g / L, 2,250 g / L, 2,000 g / L, 1,750 g / L, 1,500 g / L, 1,250 g / L, 1,000 g / L, 750 g / L, 500 g / L, 250 g / L, 200 g / L, 150 g / L, 100 g / L, 50 g / L or a range between any two of these values.

[0100] If a carbon-based compound having a solubility within the above range is used, a uniform coating can be formed more easily.

[0101] In addition, the carbon-based compound needs to be carbonized within the heat treatment temperature of step (c). If uncarbonized carbon-based compound remains in the positive electrode active material, the improvement in conductivity may be minimal or unexpected side effects may occur.

[0102] Next, the step (b) is a step of crushing the particles in the slurry, wherein the lithium-containing raw material, the iron-containing precursor, the dopant-containing raw material, the sodium-containing raw material, etc. may be present in the slurry in the form of particles.

[0103] In order to pulverize the above particles, a dry or wet dispersion mill such as a ball mill, a bead mill (beads commonly used for pulverizing metallic raw materials such as aluminum beads, iron beads or zirconium beads can be used), a vibratory mill, an attritor mill, an air jet mill, a disk mill or an air classifier mill can be used.

[0104] The average particle size (D50) of the particles crushed in the step (b) may be less than 1 μm, for example, 1.0 μm, 0.9 μm, 0.8 μm, 0.7 μm, 0.6 μm, 0.5 μm, 0.4 μm, 0.3 μm, 0.2 μm, 0.1 μm or a range between any two of these values.

[0105] The particles pulverized to have an average particle size within the above range are easily aggregated due to surface energy. During the calcination process, the aggregated particles grow into horn shapes, resulting in a decrease in the density of the positive electrode active material.

[0106] If the slurry contains a specific dopant-containing raw material, the aggregation of the particles can be suppressed. As a result, the particles grow into spherical shapes, and the density characteristics can be improved.

[0107] On the other hand, at least a portion of the above-mentioned dopant or sodium may be doped during the above-mentioned pulverization process.

[0108] On the other hand, after the pulverization in step (b), the slurry may be dried to obtain a powder form. For example, the slurry may be dried by spray drying. That is, the particles in step (c) may be obtained by spray drying the pulverized slurry in step (b).

[0109] Spray drying as an example of the above-mentioned drying can be carried out in a spray dryer. As the above-mentioned spray dryer, there is no particular limitation as long as it is a spray drying device that can prepare nearly spherical dry particles by spray-drying the above-mentioned slurry containing the above-mentioned crushed particles. For example, an ultrasonic sprayer, a single-fluid nozzle sprayer, a two-fluid nozzle sprayer, an ultrasonic nozzle sprayer, a filter expansion droplet generator (FEAG) or a disc droplet generator can be used.

[0110] The spray dryer may include a spray nozzle and a drying chamber, and the slurry is atomized into droplets of a predetermined size through the spray nozzle and sprayed into the drying chamber where a relatively high temperature gas flows.

[0111] The raw material in the liquid droplets sprayed into the drying chamber may be dried into nearly spherical particles under the temperature environment in the drying chamber.

[0112] On the other hand, if the slurry contains a specific dopant-containing raw material, unnecessary aggregation of the particles during spray drying can be suppressed, and as a result, particles close to spherical shapes can be obtained.

[0113] Here, when the viscosity of the slurry is adjusted after the pulverization in step (b) is completed, the aggregation time during drying can be shortened, and the decrease in density due to water loss during drying can be minimized.

[0114] Water loss during drying reduces particle density and forms pores. As a result, particle strength may decrease, leading to insufficient stability of the positive electrode active material.

[0115] On the other hand, if the viscosity of the slurry is too high, the fluidity decreases during drying, resulting in insufficient process efficiency and difficulty in obtaining spherical particles.

[0116] One of the methods for adjusting the viscosity of the above slurry is to add a binder.

[0117] On the other hand, at least a portion of the above-mentioned dopant or sodium may be doped during the above-mentioned spray drying process.

[0118] Subsequently, the step (c) may be a step of heat-treating the particles pulverized in the step (b) to form a lithium composite phosphorus oxide.

[0119] On the other hand, during the heat treatment process of the above step (c), at least a portion of the above dopant or sodium may be doped or coated.

[0120] In addition, during the heat treatment in the above step (c), the above carbon-based compound may be carbonized to form a carbon coating.

[0121] The heat treatment in the step (c) may be performed in an inert atmosphere at a maximum temperature of 600° C. to 900° C. for 5 to 15 hours. At this time, the maximum temperature may vary depending on the composition of the target positive electrode active material.

[0122] More specifically, the heat treatment in the above step (c) may be performed in a sintering furnace while maintaining an inert atmosphere while increasing the temperature to 600° C. to 900° C. at a rate of 1° C. to 10° C. per minute for 5 to 15 hours.

[0123] The heat treatment in the above step (c) can be carried out at a temperature of 600°C to 900°C, for example, 600°C, 625°C, 650°C, 675°C, 700°C, 725°C, 750°C, 775°C, 800°C, 825°C, 850°C, 875°C, 900°C or a range between two values.

[0124] When a specific dopant is included and heat-treated at a temperature within the above range, localized large-particle growth can be easily achieved.

[0125] When the heat treatment temperature of the step (c) is lower than 600° C., since the calcination of the precursor is not sufficiently performed, the crystal growth of the lithium composite phosphorus oxide may be insufficient, or it may be difficult to form a carbon coating layer.

[0126] On the other hand, when the heat treatment temperature in the step (c) exceeds 900° C., the lithium composite phosphorus oxide may be thermally decomposed, resulting in a decrease in particle strength or particle collapse.

[0127] On the other hand, the above-mentioned heat treatment can be carried out by increasing the temperature at a rate of 1°C to 10°C per minute, for example, at a rate of 1°C, 1.5°C, 2°C, 2.5°C, 3°C, 3.5°C, 4°C, 4.5°C, 5°C, 5.5°C, 6°C, 6.5°C, 7°C, 7.5°C, 8°C, 8.5°C, 9°C, 9.5°C, 10°C or a temperature in a range between any two of these values ​​per minute.

[0128] In addition, the above-mentioned heat treatment can be carried out by maintaining the maximum temperature for a time of less than 15 hours, for example, by maintaining the maximum temperature for 15 hours, 14.5 hours, 14 hours, 13.5 hours, 13 hours, 12.5 hours, 12 hours, 11.5 hours, 11 hours, 10.5 hours, 10 hours, 9.5 hours, 9 hours, 8.5 hours, 8 hours, 7.5 hours, 7 hours, 6.5 hours, 6 hours, 5.5 hours, 5 hours or a time range between any two of these values.

[0129] Here, for example, the inert atmosphere may be formed by replacing air with at least one inert gas selected from the group consisting of N 2 , Ar, He, Rn, Ne, and Xe, but is not limited thereto.

[0130] Optionally, in the above step (c), before the above particles crushed in the above step (b) are heat-treated, at least one auxiliary raw material selected from the group consisting of Ag, Al, As, Au, B, Ba, Be, Bi, Ca, Cd, Ce, Co, Cr, Cu, F, Fe, Ga, Hf, I, In, K, La, Mg, Mo, N, Na, Nb, Nd, Ni, Os, Pd, Pr, Pt, Rh, Ru, Si, Sm, Sn, Sr, Ta, Ti, V, W, Y, Zn and Zr and at least one of the lithium-containing raw materials may be further added. The above auxiliary raw materials may be provided in the form of at least one selected from sulfates, carbonates, nitrates, acetates, chlorides, hydroxides and oxides.

[0131] At this time, the content of the auxiliary material added in the step (c) may vary depending on the composition of the particles and the composition of the target positive electrode active material.

[0132] Therefore, when the mixture of the particles and the auxiliary material is heat treated in the step (c), the elements contained in the auxiliary material may be doped into the lithium composite phosphorus oxide or may be coated on at least a portion of the surface of the lithium composite phosphorus oxide.

[0133] The lithium complex phosphorus compound obtained in the step (c) may include primary particles and secondary particles formed by agglomeration of the primary particles. The lithium complex phosphorus compound may be represented by the following chemical formula 2, but is not limited thereto.

[0134] [Chemical formula 2]

[0135] Li p Fe (1-y-z) M y Na z PO4

[0136] (In the above formula, M is at least one selected from the group consisting of Ag, Al, As, Au, Ba, Be, Bi, Ca, Cd, Ce, Co, Cr, Cu, Ga, Hf, In, K, La, Mg, Mo, Nb, Nd, Ni, Os, Pd, Pr, Pt, Rh, Ru, Si, Sm, Sn, Sr, Ta, Ti, V, W, Y, Zn and Zr, 0.95≤p≤1.05, 0.02≤y≤0.03, 0≤z≤0.01)

[0137] In addition, before or after the step (c), the lithium composite phosphorus oxide may be subjected to a pulverization (disintegration), classification (distribution) and / or water washing process.

[0138] Positive electrode active material for lithium secondary battery

[0139] A positive active material for a lithium secondary battery according to another aspect may include a lithium composite phosphorus oxide capable of intercalating / deintercalating lithium ions.

[0140] The lithium composite phosphorus oxide contained in the positive electrode active material includes secondary particles formed by aggregation of a plurality of primary particles.

[0141] That is, the positive electrode active material is provided as an aggregate including primary particles composed of a lithium complex phosphorus oxide capable of absorbing and desorbing lithium ions and secondary particles formed by aggregating the primary particles.

[0142] In one example, the primary particles may have a spherical shape. As described above, since the lithium composite phosphorus oxide is a particle having a smooth surface, the positive electrode active material may have an excellent particle density.

[0143] Here, the average particle size of the primary particles (wherein the average particle size of the primary particles may be the average major axis length of the primary particles) is 0.05 μm to 0.5 μm, for example, 0.05 μm, 0.1 μm, 0.15 μm, 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, 0.5 μm or in a range between any two of these values, so that the optimal density of the positive electrode prepared using the positive electrode active material according to various embodiments can be achieved.

[0144] On the other hand, the primary particles may have a bimodal form including the first lithium complex phosphorus oxide as small particles and the second lithium complex phosphorus oxide as large particles.

[0145] In this case, small particles having a relatively small average particle size can fill the gaps between large particles, thereby increasing the integration density of the lithium composite phosphorus oxide per unit volume, and thus the energy density per unit volume can be increased.

[0146] Here, the large particles may refer to primary particles having a particle size of 3 μm to 20 μm.

[0147] On the other hand, the small particles mentioned above may refer to primary particles having a particle size of 1 μm or less.

[0148] The lithium composite phosphorus oxide may include particles having a particle size outside the above range, but the peak of the particle size distribution may fall within the particle size range of each of the large particles and the small particles.

[0149] Pores and / or grain boundaries may exist between the primary particles constituting the secondary particles. In another embodiment, the positive electrode active material may include a lithium composite phosphorus oxide in the form of a single crystal having an average particle size of 0.05 μm or more.

[0150] The primary particles may be spaced apart from adjacent primary particles in the interior of the secondary particles to form internal pores. In addition, the primary particles may form a surface present in the interior of the secondary particles by contacting the internal pores, without forming a grain boundary by contacting adjacent primary particles. On the other hand, the surface of the primary particles present in the outermost surface of the secondary particles exposed to the external air forms the surface of the secondary particles.

[0151] The average particle size of the secondary particles formed by the agglomeration of multiple primary particles mentioned above may vary depending on the number of agglomerated primary particles, but may generally be between 30.0 μm and 40.0 μm. For example, it may be 30.0 μm, 30.5 μm, 31.0 μm, 31.5 μm, 32.0 μm, 32.5 μm, 33.0 μm, 33.5 μm, 34.0 μm, 34.5 μm, 35.0 μm, 35.5 μm, 36.0 μm, 36.5 μm, 37.0 μm, 37.5 μm, 38.0 μm, 38.5 μm, 39.0 μm, 39.5 μm, 40.0 μm or a range between any two of these values.

[0152] On the other hand, in the above-mentioned positive electrode active material, the content of the above-mentioned first lithium composite phosphorus oxide can be 80 wt % to 90 wt %, for example, 80 wt %, 80.5 wt %, 81 wt %, 81.5 wt %, 82 wt %, 82.5 wt %, 83 wt %, 83.5 wt %, 84 wt %, 84.5 wt %, 85 wt %, 85.5 wt %, 86 wt %, 86.5 wt %, 87 wt %, 87.5 wt %, 88 wt %, 88.5 wt %, 89 wt %, 89.5 wt %, 90 wt % or a range between any two of these values.

[0153] For example, in the above-mentioned positive electrode active material, the content of the above-mentioned second lithium composite phosphorus oxide can be 10 wt % to 20 wt %, for example, 10 wt %, 10.5 wt %, 11 wt %, 11.5 wt %, 12 wt %, 12.5 wt %, 13 wt %, 13.5 wt %, 14 wt %, 14.5 wt %, 15 wt %, 15.5 wt %, 16 wt %, 16.5 wt %, 17 wt %, 17.5 wt %, 18 wt %, 18.5 wt %, 19 wt %, 19.5 wt %, 20 wt % or a range between two values.

[0154] When the contents of the first lithium composite phosphorus oxide and the second lithium composite phosphorus oxide satisfy the above ranges, the density of the positive electrode active material can be high.

[0155] In addition, at least one of the first lithium composite phosphorus oxide and the second lithium composite phosphorus oxide may include iron, a dopant, and sodium.

[0156] The above-mentioned dopant is at least one selected from the group consisting of Ag, Al, As, Au, Ba, Be, Bi, Ca, Cd, Ce, Co, Cr, Cu, Ga, Hf, In, K, La, Mg, Mo, Nb, Nd, Ni, Os, Pd, Pr, Pt, Rh, Ru, Si, Sm, Sn, Sr, Ta, Ti, V, W, Y, Zn and Zr.

[0157] According to the above preparation method, when the lithium composite phosphorus oxide particles are grown using the iron-containing precursor, the particle size can be adjusted using a dopant and sodium.

[0158] That is, the lithium composite phosphorus oxide may be synthesized into a bimodal form including small particles and large particles by including iron, a dopant, and a sodium element.

[0159] In addition, the dopant and the sodium element can adjust the crystallinity of the lithium composite phosphorus oxide.

[0160] On the other hand, the lithium composite phosphorus oxide can be represented by the following Chemical Formula 2.

[0161] [Chemical formula 2]

[0162] Li p Fe (1-y-z) M y Na z PO4

[0163] In the above formula, M is at least one selected from the group consisting of Ag, Al, As, Au, Ba, Be, Bi, Ca, Cd, Ce, Co, Cr, Cu, Ga, Hf, In, K, La, Mg, Mo, Nb, Nd, Ni, Os, Pd, Pr, Pt, Rh, Ru, Si, Sm, Sn, Sr, Ta, Ti, V, W, Y, Zn and Zr, 0.95≤p≤1.05, 0.02≤y≤0.03, 0≤z≤0.01.

[0164] The composition of the lithium composite phosphorus oxide may vary depending on the composition of the raw material used in the above-mentioned preparation method and the type and composition of the auxiliary raw material additionally used therein.

[0165] Furthermore, the positive electrode active material may include a coating layer covering at least a portion of the surface of the primary particles (eg, interfaces between the primary particles) and / or secondary particles formed by agglomerating the primary particles.

[0166] In addition, an amorphous carbon coating with a thickness of 1 nm to 500 nm, for example, a thickness of 1 nm, 1.5 nm, 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm, 5.5 nm, 6 nm, 6.5 nm, 7 nm, 7.5 nm, 8 nm, 8.5 nm, 9 nm, 9.5 nm, 10 nm, 12.5 nm, 15 nm, 17.5 nm, 20 nm, 22.5 nm, 25 nm, 50 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm or a range between two values ​​may be formed on the surface of at least a portion of the primary particles.

[0167] For example, the coating layer may exist in a manner of covering at least a portion of the exposed surface of the primary particle. In particular, the coating layer may exist in a manner of covering at least a portion of the exposed surface of the primary particle at the outermost periphery of the secondary particle.

[0168] Thus, the coating layer may exist as a layer that continuously or discontinuously coats the surface of the primary particles and / or the secondary particles formed by agglomerating the primary particles. When the coating layer exists discontinuously, it may exist in the form of islands.

[0169] Furthermore, depending on circumstances, the oxide may exist not only at the interface between the primary particles and at least a portion of the surface of the secondary particles, but also in internal voids formed in the secondary particles.

[0170] The presence of the coating in this manner can contribute to improving the electrochemical characteristics and stability of the positive electrode active material.

[0171] The coating layer may exist in the form of a solid solution without forming a boundary with the primary particles and / or the secondary particles formed by agglomerating the primary particles, but the coating layer is not necessarily limited thereto.

[0172] In particular, the low conductivity of lithium iron phosphate-based positive active materials can be compensated by carbon coating. However, uneven carbon coating may deteriorate the properties of the positive active materials such as BET specific surface area, particle density and energy capacity.

[0173] For example, the content of the above-mentioned carbon coating layer is 1.0 wt% to 2.0 wt% based on 100 wt% of the above-mentioned lithium composite phosphorus oxide, for example, 1.0 wt%, 1.05 wt%, 1.1 wt%, 1.15 wt%, 1.2 wt%, 1.25 wt%, 1.3 wt%, 1.35 wt%, 1.4 wt%, 1.45 wt%, 1.5 wt%, 1.55 wt%, 1.6 wt%, 1.65 wt%, 1.7 wt%, 1.75 wt%, 1.8 wt%, 1.85 wt%, 1.9 wt%, 1.95 wt%, 2.0 wt%, or a range between any two of these values.

[0174] When the above range is satisfied, the electrical conductivity of the lithium composite phosphorus oxide can be improved, and at the same time, the decrease in the particle density of the positive electrode active material can be minimized.

[0175] On the other hand, in the positive electrode active material, the first lithium composite phosphorus oxide and the second lithium composite phosphorus oxide may be coated with the same amount of carbon.

[0176] The thickness of the carbon coating layer can be adjusted according to the balance between the fluidity and the conductivity of the lithium composite phosphorus oxide.

[0177] The thickness of the carbon coating can be measured using a variety of known methods. For example, it can be measured by TEM or SEM images, or confirmed by EDX analysis results or line scanning inspection results of carbon in a specific direction. The thickness as described above can be an average value after at least 3 measurements.

[0178] Lithium secondary battery

[0179] According to another aspect, a positive electrode including a positive electrode collector and a positive electrode active material layer formed on the positive electrode collector may be provided, wherein the positive electrode active material layer may include a positive electrode active material prepared by the preparation method according to various embodiments as the positive electrode active material.

[0180] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has electrical conductivity. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, or the surface of aluminum or stainless steel may be surface treated with carbon, nickel, titanium, silver, etc. In addition, the positive electrode current collector may generally have a thickness of 3 μm to 500 μm, and fine concavoconvexities may be formed on the surface of the current collector to improve the binding force of the positive electrode active material. For example, it may be used in various forms such as a film, a sheet, a foil, a net, a porous body, a foam, and a nonwoven body.

[0181] The positive electrode active material layer may be prepared by coating a positive electrode slurry composition including the positive electrode active material, a conductive material, and optionally a binder as required, on the positive electrode current collector.

[0182] In this case, the content of the positive electrode active material can be 80 wt % to 99 wt %, more specifically 85 wt % to 98.5 wt % relative to the total weight of the positive electrode active material layer. When the positive electrode active material is included in the above content range, excellent capacity performance can be shown, but it is not limited thereto.

[0183] The above-mentioned conductive materials are used to impart conductivity to the electrode. In the battery formed, as long as they do not cause chemical changes and have electronic conductivity, they can be used without limitation. As specific examples, graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, etc., and one of them or a mixture of two or more thereof can be used. The above-mentioned conductive material may be included in an amount of 0.1% to 15% by weight relative to the total weight of the positive electrode active material layer.

[0184] The above-mentioned binder plays a role in improving the adhesion between multiple positive electrode active material particles and the bonding force between the positive electrode active material and the collector. As a specific example, polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile (polyacrylonitrile), carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated ethylene propylene diene rubber, styrene butadiene rubber (SBR), fluororubber or various copolymers thereof, etc., can be used. One or a mixture of two or more thereof. Relative to the total weight of the positive electrode active material layer, 0.1% to 15% by weight of the above-mentioned binder may be included.

[0185] In addition to using the above-mentioned positive electrode active material, the above-mentioned positive electrode can be prepared according to a common positive electrode preparation method. Specifically, it can be prepared by coating a positive electrode slurry composition on a positive electrode collector and then drying and rolling it. The above-mentioned positive electrode slurry composition is prepared by dissolving or dispersing the above-mentioned positive electrode active material in a solvent and selectively dissolving or dispersing a binder and a conductive material in a solvent.

[0186] The above-mentioned solvent may be a solvent commonly used in the art, and examples thereof include dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone or water, and a mixture of one or more thereof may be used. Considering the coating thickness and preparation yield of the slurry, the amount of the above-mentioned solvent used is sufficient to dissolve or disperse the above-mentioned positive electrode active material, conductive material and binder and have a viscosity that can show excellent thickness uniformity when coated for the preparation of the positive electrode.

[0187] Furthermore, in another embodiment, the positive electrode may be prepared by casting the positive electrode slurry composition on a separate support, and then laminating a thin film obtained by peeling the support on a positive electrode collector.

[0188] In addition, according to another aspect of the present invention, an electrochemical device comprising the positive electrode described above can be provided. Specifically, the electrochemical device described above can be a battery, a capacitor, etc., and more specifically, can be a lithium secondary battery.

[0189] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode disposed opposite to the positive electrode, and a separation membrane and an electrolyte interposed between the positive electrode and the negative electrode.

[0190] In addition, the lithium secondary battery can be provided as an anode-free secondary battery. The positive electrode is the same as the above description, so for convenience, the specific description is omitted, and only the remaining configuration not mentioned above is described below. In addition, the description related to the negative electrode to be described below should be understood as being described on the premise that the negative electrode is present in the lithium secondary battery.

[0191] On the other hand, the lithium secondary battery may be a lithium secondary battery using a solid electrolyte instead of a separator. In this case, an electrode slurry composition to which an additional solid electrolyte is added may be used when preparing the positive electrode and the negative electrode.

[0192] The lithium secondary battery may further include: a battery container for accommodating the electrode assembly of the positive electrode, the negative electrode and the separation membrane; and a sealing member for sealing the battery container.

[0193] The negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0194] The negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, the negative electrode current collector can usually have a thickness of 3μm to 500μm. Similar to the positive electrode current collector, the binding force of the negative electrode active material can be strengthened by forming fine concave and convex on the surface of the collector. For example, it can be used in various forms such as film, sheet, foil, net, porous body, foam, non-woven body, etc.

[0195] The negative electrode active material layer may be prepared by coating a negative electrode slurry composition including the negative electrode active material and a conductive material and optionally including a binder as required on the negative electrode collector.

[0196] As the negative electrode active material, a compound capable of reversibly inserting and extracting lithium can be used. Specific examples include carbon materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metal compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, or Al alloys; such as SiO β (0<β<2), SnO2, vanadium oxide, lithium vanadium oxide, metal oxides capable of being doped and dedoped with lithium; or composites containing the above metal compounds and carbon materials such as Si-C composites or Sn-C composites, etc., and one or a mixture of two or more of them can be used. In addition, as the above-mentioned negative electrode active material, a metal lithium film can also be used. In addition, both low-crystalline carbon and high-crystalline carbon can be used as carbon materials. Representative low-crystalline carbons are soft carbon and hard carbon, and representative high-crystalline carbons are amorphous, plate-like, flaky, spherical or fibrous natural graphite or artificial graphite, condensed graphite (Kishgraphite), pyrolytic carbon (pyrolytic carbon), mesophase pitch based carbon fiber (mesophase pitch based carbon fiber), mesophase carbon microbeads (meso-carbon microbeads), mesophase pitch (Me sophase pitches) and petroleum or coal tar pitch derived cokes (petroleum or coal tar pitch derived cokes) and other high-temperature sintered carbons.

[0197] The negative electrode active material layer may contain 80 wt % to 99 wt % of the negative electrode active material, based on the total weight of the negative electrode active material layer.

[0198] The binder is a component that helps to bind the conductive material, the active material and the collector. Usually, based on the total weight of the negative electrode active material layer, 0.1 wt % to 10 wt % of the binder can be added. Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber, sulfonated ethylene propylene diene rubber, styrene butadiene rubber, nitrile rubber, fluororubber, and various copolymers thereof.

[0199] The conductive material is a component used to further improve the conductivity of the negative electrode active material. Based on the total weight of the negative electrode active material layer, the conductive material can be added in an amount of 10% by weight or less, preferably 5% by weight or less. There are no particular restrictions on such conductive materials as long as they do not induce chemical changes in the corresponding battery and have conductivity. For example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black; conductive fibers such as carbon fibers or metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, etc. can be used.

[0200] In one embodiment, the negative electrode active material layer can be prepared by coating a negative electrode slurry composition on a negative electrode collector and drying it, wherein the negative electrode slurry composition is prepared by dissolving or dispersing the negative electrode active material in a solvent and selectively dissolving or dispersing a binder and a conductive material in a solvent, or by casting the negative electrode slurry composition on a separate support and laminating a thin film obtained by peeling off the support on the negative electrode collector.

[0201] On the other hand, in the above-mentioned lithium secondary battery, the separation membrane is used to separate the negative electrode and the positive electrode and provide a mobile channel for lithium ions. As long as the separation membrane commonly used in the lithium secondary battery, it can be used without restriction, especially, preferably, for the ion movement of the electrolyte, the impedance is low and there is excellent electrolyte moisture-containing capacity. Specifically, a porous polymer film can be used, for example, a porous polymer film prepared by polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers or their two or more layers of stacked structures. In addition, a common porous non-woven fabric can also be used, for example, a non-woven fabric made of high melting point glass fiber, polyethylene terephthalate fiber, etc. In addition, in order to ensure heat resistance or mechanical strength, a separation membrane comprising a ceramic component and a coated polymer substance can also be used, which can be selectively used with a single layer or multilayer structure.

[0202] Furthermore, examples of the electrolyte used in the present invention include, but are not limited to, organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in preparing lithium secondary batteries.

[0203] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0204] As the above-mentioned organic solvent, any organic solvent that can act as a medium for the movement of ions involved in the electrochemical reaction of the battery can be used without limitation. Specifically, as the above-mentioned organic solvent, ester solvents such as methylacetate, ethyl acetate, γ-butyrolactone, ε-caprolactone, etc.; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (EPC), etc. can be used. Carbonate solvents such as nate, PC, etc.; alcohol solvents such as ethanol and isopropanol; nitriles such as R-CN (r is a straight-chain, branched or cyclic hydrocarbon group with 2 to 20 carbon atoms, which may contain a double-bonded aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolane, etc. Among them, carbonate solvents are preferred, and more preferably, a mixture of cyclic carbonates (such as ethylene carbonate or propylene carbonate, etc.) with high ionic conductivity and high dielectric constant that can improve the charge and discharge performance of the battery, and low-viscosity linear carbonate compounds (such as ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate, etc.). In this case, when the cyclic carbonate and the chain carbonate are mixed in a volume ratio of about 1:1 to about 1:9, excellent electrolyte performance can be shown.

[0205] The above-mentioned lithium salt can be used without limitation as a compound that can provide lithium ions used in a lithium secondary battery. Specifically, the above-mentioned lithium salt can be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI or LiB(C2O4)2, etc. Preferably, the concentration of the above-mentioned lithium salt is used in the range of 0.1M to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, and therefore, excellent electrolyte performance can be shown, and lithium ions can be effectively moved.

[0206] In addition to the above electrolyte components, the electrolyte may further include one or more additives such as halogenated alkylene carbonate compounds such as bisfluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol or aluminum chloride, etc., for the purpose of improving the life characteristics of the battery, inhibiting the reduction of the battery capacity, and increasing the discharge capacity of the battery. In this case, the above additives may be included in an amount of 0.1 wt % to 5 wt % relative to the total weight of the electrolyte.

[0207] On the other hand, the above-mentioned electrolyte may include a solid electrolyte such as a solid polymer electrolyte, a gel-type polymer electrolyte, or a solid inorganic electrolyte.

[0208] A lithium secondary battery containing a solid electrolyte can omit the above-mentioned separation membrane. However, since it is difficult for the electrolyte to penetrate into the positive electrode and the negative electrode, the electrode can be formed by mixing the solid electrolyte when manufacturing the electrode.

[0209] On the other hand, the solid polymer electrolyte or gel polymer electrolyte can be a composite of a salt of a metal ion of Group 1 or Group 2 of the periodic table and a polymer resin. For example, it can be formed by adding a polymer resin to a solvated lithium salt.

[0210] The salts of the above-mentioned metal ions can be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI or LiB(C2O4)2, etc.

[0211] For example, examples of the above-mentioned polymer resin can be polyether polymers, polycarbonate polymers, acrylic polymers, polysiloxane polymers, phosphazene polymers, polyethylene derivatives, alkyl oxide derivatives such as polyethylene glycol, phosphate polymers, polyagitation lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, polymers containing ionic dissociative groups, branched copolymers in which amorphous polymers such as PMM A, polycarbonate, polysiloxane (PDMS) or phosphazene are copolymerized as comonomers in the PEO (polyethylene glycol) main chain, comb-like polymer resins, and cross-linked polymer resins.

[0212] As the solid inorganic electrolyte, generally, a sulfide-based solid electrolyte and an oxide-based solid electrolyte can be used.

[0213] Sulfide-based solid electrolytes may be materials containing sulfur (S) and having conductivity of metal ions of Group 1 or Group 2 of the periodic table used in secondary batteries, such as Li-PS-based glass or Li-PS-based glass ceramics having lithium ion conductivity.

[0214] Examples of the above-mentioned sulfide-based solid electrolyte may be at least one selected from the group consisting of Li6PS5Cl, Li6PS5Br, Li6PS5I, Li2S-P2S5, Li2S-LiI-P2S5, Li2S-LiI-Li2O-P2S5, Li2S-Li Br-P2S5, Li2S-Li2OP2S5, Li2S-Li3PO4-P2S5, Li2S-P2S5-P2S5, Li2S-P2S5-SiS2, Li2S-P2S5-SnS, Li2S-P2S5-Al2S3, Li2S-GeS2 and Li2S-GeS2-ZnS.

[0215] On the other hand, the oxide-based solid electrolyte may be a material containing oxygen (O) and having the conductivity of metal ions of Group 1 or Group 2 of the periodic table used in secondary batteries. For example, examples of the above-mentioned oxide-based solid electrolyte may be selected from LLTO-based compounds, Li6La2CaTa2O 12 、Li6La2ACaNb2O 12 、Li6La2ASrNb2O 12 、Li2Nd3TeSbO 12 、Li3BO 2.5 N 0.5 , Li9SiAlO8, LAGP-based compounds, LATP-based compounds, LISICON-based compounds, LIPON-based compounds, perovskite-based compounds, NASICO-based compounds and LLZO-based compounds.

[0216] As described above, the lithium secondary battery containing the above-mentioned positive electrode active material stably shows excellent discharge capacity, output characteristics and life characteristics, and therefore can be used in portable devices such as mobile phones, notebook computers, digital cameras and electric vehicle fields such as hybrid electric vehicles (HEV).

[0217] The shape of the lithium secondary battery is not particularly limited, and may be a cylindrical can, a prismatic can, a pouch can, a coin can, etc. Preferably, the lithium secondary battery can be used not only as a battery cell used as a power source for small devices, but also as a unit battery of a medium or large battery module including a plurality of battery cells.

[0218] According to another aspect, a battery module including the above-described lithium secondary battery as a unit cell and / or a battery pack including the same may be provided.

[0219] The battery module or the battery pack can be used as a power tool; an electric vehicle including an electric vehicle (EV), a hybrid electric vehicle and a plug-in hybrid electric vehicle (PHEV); or a power source for one or more medium or large devices in a power storage system.

[0220] Hereinafter, the present invention will be described in more detail by way of examples. However, these examples are only for illustrating the present invention, and the scope of the present invention should not be construed as being limited by these examples.

[0221] Preparation Example 1. Preparation of positive electrode active material

[0222] (1) Comparative Example 1

[0223] FeSO4·7H2O, H3PO4 and H2O2 are added to the reactor so that the molar ratio of FeSO4·7H2O, H3PO4 and H2O2 is 1:1:1, and then pure water (DIW) is added to prepare an aqueous solution. NaOH and NH4OH are added to the above solution and stirred. At this time, the temperature in the reactor is maintained at 60°C, and N2 gas is introduced to synthesize the precursor. After the reaction is completed, washing and dehydration are performed to obtain a transition metal hydroxide precursor composed of FePO4·xH2O.

[0224] The transition metal hydroxide precursor was heat treated for 5 hours in a calcining furnace in a N2 atmosphere while the temperature was raised to 550°C at a rate of 2°C / min and maintained at the temperature, and then the iron-containing precursor was obtained by furnace cooling.

[0225] The iron-containing precursor, the lithium-containing raw material, i.e., Li2CO3, and the carbon-based compound, i.e., glucose, were mixed so that their molar ratio was 2:1:1 to prepare a slurry. Then, the precursor and the raw material in the slurry were pulverized using a ball mill so that their D50 was less than 1.0 μm. Then, the slurry was dried using a spray dryer (Dongjin Technology Co., Ltd., Korea, DJE003R).

[0226] The mixture was heat treated for 8 hours in a calcination furnace in a N2 atmosphere while being heated to 850°C at a rate of 2°C / min and maintained at this temperature. Then, the mixture was furnace cooled and classified to obtain a positive electrode active material containing lithium iron phosphate with a D50 of 30.0 μm to 40.0 μm.

[0227] (2) Comparative Example 2

[0228] A positive electrode active material was prepared in the same manner as in Comparative Example 1, except that the titanium-containing raw material was mixed so that the molar ratio of iron to titanium in the slurry was 97:3.

[0229] (3) Embodiment 1

[0230] The positive electrode active material was prepared in the same manner as in Comparative Example 1, except that the titanium-containing raw material and the sodium-containing raw material were mixed so that the molar ratio of iron, titanium and sodium in the slurry was 97:2.5:0.5.

[0231] (4) Embodiment 2

[0232] The positive electrode active material was prepared in the same manner as in Comparative Example 1, except that the vanadium-containing raw material and the sodium-containing raw material were mixed so that the molar ratio of iron, vanadium and sodium in the slurry was 97:2.5:0.5.

[0233] (5) Embodiment 3

[0234] The positive electrode active material was prepared in the same manner as in Comparative Example 1, except that the magnesium-containing raw material and the sodium-containing raw material were mixed so that the molar ratio of iron, magnesium and sodium in the slurry was 97:2.5:0.5.

[0235] (6) Embodiment 4

[0236] The positive electrode active material was prepared in the same manner as in Comparative Example 1, except that the aluminum-containing raw material and the sodium-containing raw material were mixed so that the molar ratio of iron, aluminum and sodium in the slurry was 97:2.5:0.5.

[0237] (7) Embodiment 5

[0238] The positive electrode active material was prepared in the same manner as in Comparative Example 1, except that the zinc-containing raw material and the sodium-containing raw material were mixed so that the molar ratio of iron, zinc and sodium in the slurry was 97:2.5:0.5.

[0239] In the above-mentioned Examples 1 to 5, sulfates, carbonates, nitrates, acetates, chlorides, hydroxides and oxides were used as raw materials containing specific elements.

[0240] Experimental Example 1. Characteristic Analysis of Positive Electrode Active Material

[0241] In order to confirm the characteristics of the positive electrode active material prepared according to Preparation Example 1, the crystallite size was analyzed by XRD and is shown in Table 1 below.

[0242] Table 1

[0243]

[0244] In addition, for the above positive electrode active material, the average particle size and particle size distribution of the primary particles and secondary particles of the prepared positive electrode active material were measured using a laser diffraction scattering particle size distribution analyzer (Cilas PSA1060), and a volume-based cumulative particle size distribution curve was obtained. The results are shown in Table 2 and Figure 1 and Figure 2 shown.

[0245] Table 2

[0246]

[0247]

[0248] On the other hand, in the primary particles of Examples, the ratio of particles having a particle size of 1 μm or less and the ratio of particles having a particle size of 3 μm or more are shown in Table 3 below.

[0249] Table 3

[0250] Classification Example 1 Example 2 Example 3 Example 4 Example 5 1μm or less (%) 80.41 80.24 80.51 80.48 80.35 3μm or more (%) 18.33 18.08 16.18 16.35 17.21

[0251] In addition, the sizes of primary particles were measured from cross-sectional SEM images of the positive electrode active materials prepared in the above-mentioned Comparative Examples and Examples. The results are shown in Table 4 below.

[0252] Table 4

[0253]

[0254] From the above results, it was confirmed that bimodal primary particles were produced in the positive electrode active material of the example doped with a dopant that can function as a flux.

[0255] In particular, referring to Comparative Example 2 and Examples 1 to 5, it was confirmed that large particles can be prepared by adding Na as a dopant.

[0256] In addition, even when Na dopant was added, no problems such as lattice distortion or residual impurities were found.

[0257] Preparation Example 2. Preparation of lithium secondary battery

[0258] 94 wt % of each positive electrode active material prepared according to Preparation Example 1, 3 wt % of artificial graphite and 3 wt % of PVDF binder were dispersed in 3.5 g of N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode slurry. The positive electrode slurry was uniformly coated on an aluminum film having a thickness of 20 μm as a positive electrode collector and dried, and roll-pressed to prepare a positive electrode.

[0259] Relative to the above-mentioned positive electrode, lithium foil is used as a counter electrode, a porous polyethylene film (Celgard 2300, thickness: 25μm) is used as a separation membrane, and a button battery is manufactured by a conventional manufacturing process using an electrolyte solution in which LiPF6 is present at a concentration of 1.15M in a solvent of ethylene carbonate and ethyl methyl carbonate mixed in a volume ratio of 3:7.

[0260] Experimental Example 2. Evaluation of electrochemical characteristics of lithium secondary batteries

[0261] In Preparation Example 2, a charge and discharge experiment was performed on a button cell using an electrochemical analyzer (Toyo, Toscat3100) at 25°C, a voltage range of 2.0V to 3.65V, and a discharge rate of 0.1C to 5.0C, and the initial charge capacity, initial discharge capacity, initial reversible efficiency, and energy density were measured. 3 g of the positive electrode active material was weighed in a granulator and the particle density was measured after pressurizing at 4.5 tons for 5 seconds. The energy density was calculated by multiplying the initial discharge capacity by the average voltage (3.4V) and the particle density.

[0262] Table 5

[0263]

[0264] When the positive electrode active material of the embodiment to which the dopant having a flux effect is added is used, the particle density increases, and as a result, electrochemical properties such as energy density are improved.

[0265] This is considered to be because the shape of the primary particles changes, so that the positive electrode active material has a bimodal particle size.

[0266] Although the embodiments of the present specification are described above, those skilled in the art will understand that various modifications and changes can be made to the present specification by adding, modifying, deleting, increasing, etc., without departing from the scope of the ideas of the present specification as described in the claims, and these also fall within the scope of the rights of the present specification.

Claims

1. A method for preparing a positive electrode active material for a lithium secondary battery, characterized in that: include: Step (a), preparing a slurry by mixing a lithium-containing raw material, an iron-containing precursor, a dopant-containing raw material, a sodium-containing raw material and a carbon-based compound; Step (b), crushing the particles in the slurry; and Step (c), heat treating the crushed particles to obtain lithium composite phosphorus oxide; The above-mentioned dopant is at least one selected from the group consisting of Ag, Al, As, Au, Ba, Be, Bi, Ca, Cd, Ce, Co, Cr, Cu, Ga, Hf, In, K, La, Mg, Mo, Nb, Nd, Ni, Os, Pd, Pr, Pt, Rh, Ru, Si, Sm, Sn, Sr, Ta, Ti, V, W, Y, Zn and Zr.

2. The method for preparing a positive electrode active material for a lithium secondary battery according to claim 1, characterized in that: In the slurry in the step (a), a ratio (Li / Metal) of the number of lithium atoms (Li) to the total number of metal atoms (Metal) other than lithium is 0.95 to 1.

05.

3. The method for preparing a positive electrode active material for a lithium secondary battery according to claim 1, characterized in that: In the slurry in the step (a), a ratio (Fe / Metal) of the number of atoms of iron (Fe) to the total number of atoms of metal elements other than lithium (Metal) is 0.96 to 0.

98.

4. The method for preparing a positive electrode active material for a lithium secondary battery according to claim 1, characterized in that: In the slurry in the step (a), a ratio (D / Metal) of the number of atoms of the dopant (D) to the total number of atoms of metal elements (Metal) other than lithium is 0.02 to 0.

03.

5. The method for preparing a positive electrode active material for a lithium secondary battery according to claim 1, characterized in that: In the slurry in the step (a), a ratio (Na / Metal) of the number of atoms of sodium (Na) to the total number of atoms of metal elements other than lithium (Metal) is 0 to 0.

01.

6. The method for preparing a positive electrode active material for a lithium secondary battery according to claim 1, characterized in that: In the step (a), at least one of the dopant-containing raw material and the sodium-containing raw material is at least one selected from the group consisting of sulfates, carbonates, nitrates, acetates, chlorides, hydroxides and oxides.

7. The method for preparing a positive electrode active material for a lithium secondary battery according to claim 1, characterized in that: In the slurry in the step (a), a ratio (C / Metal) of the number of carbon atoms (C) to the total number of metal atoms (Metal) other than lithium is 0.25 to 1.

5.

8. The method for preparing a positive electrode active material for a lithium secondary battery according to claim 1, characterized in that: The particles pulverized in the step (c) are obtained by spray-drying the slurry obtained in the step (b).

9. The method for preparing a positive electrode active material for a lithium secondary battery according to claim 1, characterized in that: The heat treatment in the above step (c) is performed in an inert atmosphere at a maximum temperature of 600° C. to 900° C. for 5 hours to 15 hours.

10. A positive electrode active material for a lithium secondary battery, comprising a lithium composite phosphorus oxide capable of inserting / extracting lithium, wherein the positive electrode active material is characterized in that: The lithium phosphorus composite oxide includes secondary particles formed by agglomeration of a plurality of primary particles. The primary particles have a bimodal form including a first lithium complex phosphorus oxide as small particles and a second lithium complex phosphorus oxide as large particles, At least one of the first lithium composite phosphorus oxide and the second lithium composite phosphorus oxide includes iron, a dopant and sodium. The dopant is at least one selected from the group consisting of Ag, Al, As, Au, Ba, Be, Bi, Ca, Cd, Ce, Co, Cr, Cu, Ga, Hf, In, K, La, Mg, Mo, Nb, Nd, Ni, Os, Pd, Pr, Pt, Rh, Ru, Si, Sm, Sn, Sr, Ta, Ti, V, W, Y, Zn and Zr, An amorphous carbon coating layer having a thickness of 1 nm to 500 nm is formed on at least a portion of the surface of the primary particles.

11. The positive electrode active material for lithium secondary battery according to claim 10, characterized in that: The content of the second lithium composite phosphorus oxide in the positive electrode active material is 10 wt % to 20 wt %.

12. The positive electrode active material for lithium secondary battery according to claim 10, characterized in that: The lithium composite phosphorus oxide is represented by the following chemical formula 2: [Chemical formula 2] Li p Feb (1-y-z) M y So z PO4 In the above formula, M is at least one selected from the group consisting of Ag, Al, As, Au, Ba, Be, Bi, Ca, Cd, Ce, Co, Cr, Cu, Ga, Hf, In, K, La, Mg, Mo, Nb, Nd, Ni, Os, Pd, Pr, Pt, Rh, Ru, Si, Sm, Sn, Sr, Ta, Ti, V, W, Y, Zn and Zr, 0.95≤p≤1.05, 0.02≤y≤0.03, 0≤z≤0.

01.

13. A positive electrode, characterized in that: The positive electrode active material comprises the positive electrode active material according to any one of claims 10 to 12.

14. A lithium secondary battery, characterized in that: The positive electrode according to claim 13 is used.